2014
DOI: 10.1200/jco.2013.53.9452
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Local Recurrence With Conventional and Intensity-Modulated Radiation Therapy for Primary Soft-Tissue Sarcomas of the Extremity

Abstract: Purpose The use of intensity-modulated radiation therapy (IMRT) in the treatment of soft tissue sarcoma (STS) of the extremity is increasing, but no large-scale direct comparison has been reported between conventional external-beam radiation therapy (EBRT) and IMRT. Methods Between January 1996 and December 2010, 319 consecutive adult patients with primary nonmetastatic extremity STS were treated with limb-sparing surgery and adjuvant radiotherapy (RT) at a single institution. Conventional EBRT was used in 154… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 21 publications
6
88
0
4
Order By: Relevance
“…Third, the data were collected before our institution adopted intensity-modulated radiotherapy techniques for this entity. In a recent article by Folkert et al, 13 it was suggested that intensity-modulated radiotherapy could improve outcome in the setting of STS. Finally, even expert sarcoma surgeons encounter challenges when dealing with sarcoma of the buttock owing to the proximity of the sciatic nerve and the tendency for prolongations of wound closure in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the data were collected before our institution adopted intensity-modulated radiotherapy techniques for this entity. In a recent article by Folkert et al, 13 it was suggested that intensity-modulated radiotherapy could improve outcome in the setting of STS. Finally, even expert sarcoma surgeons encounter challenges when dealing with sarcoma of the buttock owing to the proximity of the sciatic nerve and the tendency for prolongations of wound closure in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Die mit IMRT behandelten Patienten waren älter (p = 0,08), hatten mehr hochgradige Tumoren (p = 0,05), mehr Resektionen mit "close margins" (< 1 mm) oder positiOriginalbeitrag Folkert MR, Singer S, Brennan MF et al (2014) Comparison of local recurrence with conventional and intensitymodulated radiation therapy for primary soft-tissue sarcomas of the extremity. J Clin Oncol 32:3236-3241…”
Section: Kommentarunclassified
“…Während bei Kopf-Hals-Tumoren [5] und der tangentialen Mammabestrahlung [6] die Vorteile einer IMRT gegenüber der konventionellen RT hinsichtlich der Toxizitätsreduktion mittlerweile in randomisierten Studien nachgewiesen wurden und auch erste Registerdaten in diese Richtung deuten [2], fehlen solche prospektiv kontrollierten Vergleiche oder Analysen von großen Patientenzahlen bei vielen anderen Tumorentitäten. Die vorliegende Arbeit [3] beschreibt die erste größere vergleichende Analyse zwischen mittels 3-D-konventioneller RT (3D-CRT) und IMRT prä-oder postoperativ bestrahlter Patienten aus dem MSKCC (Memorial Sloan Kettering Cancer Center), das über eine lange Erfahrung bei der Behandlung von WeichZiel der Arbeit Die Verwendung intensitätsmodulierter Radiotherapie (IMRT) in der Behandlung von Weichteilsarkomen (WTS) der Extremitäten nimmt zu, jedoch ist bisher kein direkter Vergleich zwischen konventioneller externer Strahlentherapie ("external beam radiotherapy", EBRT) und IMRT mit größeren Patientenzahlen veröffentlicht worden. F. Lohr, A. Simeonova teilsarkomen verfügt.…”
Section: Kommentarunclassified
“…It also promoted a decrease of 31% in the maximum and average doses released in the femur, in all patients. 10 12 (B), from the same institution, analyzed 319 patients with end-stage sarcomas treated with conservative limb surgery and adjuvant radiotherapy from 1996 to 2010. Of these, 154 were treated with conformal radiotherapy and 165 with IMRT technique.…”
Section: Introductionmentioning
confidence: 99%
“…12 (B) All patients after 2002 were treated with IMRT. Their study is the largest existing and compares the conformal and IMRT techniques.…”
Section: Introductionmentioning
confidence: 99%